RELEVANSI BERLAKUNYA UUPA DI MASYARAKAT DAN PERMASALAHANNYA - Soewito Widakdo (Perspektif, 2004)
UUPA come into being to be unification if national agrarian laws, as umbrella stipulations that arrange, confirm and settle all of agrarian issues in Indonesia. Matter of land ownership and holding, certificate, land registration, land-reform matters as well as data on land, institutional affairs and authorities. Accomplishment of agrarian reforms needs to be deeply reviewed whether UUPA enforcement is still relevant or not.